BURN VICTIMS AND SKIN DONATIONS: A LEGAL PERSPECTIVE - Magda Slabbert; Bonnie Venter (Obiter, 2021)
This article highlights the need for skin donations to treat burn wounds. South Africa has an exceptionally high number of burn wound victims per annum. The ideal way to treat burn wounds is to transplant skin from another part of the patient’s body to the affected areas (autografts). Unfortunately, this is not always possible or feasible and in those cases skin from cadavers (allografts) should be used, but this can only be done if the deceased has indicated a wish during his or her lifetime that tissue be donated for transplantation use after death. If the deceased has not indicated his or her wish to be a tissue donor, family members could be asked to consent to a donation. The article looks at the legal requirements in South Africa for a valid skin donation as well as the requirements should skin be imported owing to a lack of enough tissue donors in the country. This position is contrasted to the position in the United Kingdom with a view to establishing whether South Africa can learn from another jurisdiction concerning the procurement of skin for transplantation. The possible reasons that people do not donate skin are also touched upon.